Development of Amoxicillin-Loaded Electrospun Polyurethane/Chitosan/ beta-Tricalcium Phosphate Scaffold for Bone Tissue Regeneration - (:unkn) unknown (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2018)
Biocompatible nanocomposite electrospun fibers containing Polyurethane/Chitosan/beta-Tri calcium phosphate with diverse concentrations were designed and produced through the electrospinning process for bone tissue engineering applications. After the production process, density measurement, viscosity, electrical conductivity, and tensile strength measurement tests were carried out as physical analyses of blended solutions. The chemical structural characterization was scrutinized using Fourier transform infrared spectrometer (FTIR), and scanning electron microscopy (SEM) was used to observe the morphological details of developed electrospun scaffolds. Cell viability, attachment, and proliferation were performed using a L929 fibroblast cell line. Based on the physical, SEM, FTIR analysis, and cell culture studies, preferable nanofiber composition was selected for further studies. Amoxicillin (AMX) was loaded to that selected nanofiber composition for examination of the drug release. In comparison with other studies on similar AMX controlled products, higher drug loading and encapsulation efficiencies were obtained. It has been clearly found that the developed nanofiber composites have potential for bone tissue engineering applications.
Keywords: Bone tissue engineering; chitosan; electrospinning; polyurethane; tricalcium phosphate; NANOFIBERS; CHITOSAN; NANOPARTICLES; DELIVERY; SURFACE